SUFISME DAN KONFLIK KELUARGA: PERSPEKTIF EMOSI, CINTA, DAN PENANGANAN PERCERAIAN - Hafidz Miftahuddin, Abdul; Khozinatul Asrori (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2025)
Family conflict is an increasingly prevalent social issue in modern society, including within Muslim communities. Legal approaches often fail to address the underlying psychological roots of such conflicts. This article proposes Sufism as an alternative psychological approach to addressing domestic disputes. By emphasizing the purification of the soul (tazkiyat al- nafs), emotional regulation, and the spirituality of Divine love, Sufism is believed to offer inner peace and foster individual transformation that contributes to family harmony. Through a literature study of classical Sufi works such as those of Al-Ghazali, Rumi, and Ibn ‘Ata’illah, this article reveals that Sufism is not merely a spiritual doctrine but also a therapeutic medium relevant to conflict resolution and divorce.